THE RELATIONSHIP BETWEEN SOLAR AND VOLCANIC ACTIVITY AND THE CHRONOLOGY OF ARCHAEOLOGICAL CULTURES OF EURASIA IN THE 4TH–1ST MILLENNIA BC - Stanislav GRIGORIEV (Journal of Ancient History and Archaeology)
A well-known problem of archaeological chronology is that radiocarbon chronology differs from historical chronology. Historical chronology of the Bronze Age corresponds to dendrochronology and radiocarbon chronology in case of using Bayesian statistics of AMS dates. Therefore, it is desirable to link the chronology of Northern Eurasia on the basis of typological analysis with the chronology of those regions where it is possible to use historical sources and dendrochronology. However, due to remoteness, it is difficult to find many reliable typological analogies. Therefore, it is necessary to rely on cultures that were formed as a result of migrations caused by abrupt global climatic changes, which can be dated by dendrochronology. First of all, we are talking about major volcanic processes. Such events are most clearly manifested in tree rings, which allows us to obtain their accurate dates. The use of this approach made it possible to propose benchmarks for constructing the chronology of Eurasia for the 3rd–2nd millennia BC, which make it possible to suggest a system with younger and shorter intervals than that based on radiocarbon analysis.